A radical approach for fluorescent turn 'on' detection, differentiation and bioimaging of methanol1. Issue 33 (7th September 2015) - Kumar, Virendra; Kumar, Ajit; Diwan, Uzra; Singh, Manish Kumar; Upadhyay, K. K.
<x xml:space="preserve">Abstract</x> A Schiff base (RC) is presented herein as a smart fluorescent material for the selective detection and bioimaging of methanol. The key step behind same involves methanol induced opening of the cyclic control unit of RC resulting in the formation of a highly fluorescent moiety, RO.